Fabrication of Fe3O4@UiO-66-NH2-QCA-CuCl2 nanocomposites as a novel magnetic metal–organic framework catalyst for sustainable synthesis of 2,3-diarylquinolines - Zahra Moghadasi; Reza Mohammadi; Vicky Jain; Suhas Ballal; Munthar Kadhim Abosaoda; Abhayveer Singh; T. Krithiga; Kamal Kant Joshi (BMC Chemistry)
Abstract In this study, a novel magnetic metal–organic framework catalyst, Fe3O4@UiO-66-NH2-QCA-CuCl2, was successfully fabricated and thoroughly characterized to confirm its structural and functional properties. The catalyst combines the high surface area and tunable porosity of the UiO-66-NH2 framework with the magnetic properties of Fe3O4 and the catalytic activity of copper (II) complexes. Advanced spectroscopic techniques such as FT-IR, XRD, SEM, TEM, VSM, EDX, TGA, BET and elemental mapping were employed to identify its structure and ensure the successful integration of each component. This hybrid catalyst was applied in the efficient synthesis of 2,3-dihydroquinoline derivatives through a three-component reaction involving aryl aldehydes, aryl amines, and aryl epoxides in an ionic liquid solvent. The reaction proceeded under mild conditions and achieved excellent yields within one hour, demonstrating the catalyst’s high activity, selectivity, and recyclability. This work highlights the potential of Fe3O4@UiO-66-NH2-QCA-CuCl2 as a versatile and sustainable catalyst for the green synthesis of biologically important heterocyclic. Graphical abstract